Leveraging Research to Advance Undergraduate HRD Education: An Introduction. (May 2017) - Greer, Tomika W.; Collins, Joshua C.
The Problem: As undergraduate human resource development (HRD) programs continue to develop in the United States, faculty face challenges related to finding tools, resources, and curriculum to effectively teach the principles and practices of the field to traditional college students. Most of the existing research regarding academic programs in HRD is based on graduate programs and is, therefore, less attentive to the potential of undergraduate programs as a viable pathway to the HRD profession. Little scholarship exists to address this important, pressing, and timely issue. The Solution: This issue of Advances in Developing Human Resources addresses the gap in knowledge regarding better practices for teaching and learning in undergraduate HRD programs and contains the first collection of focused examinations of HRD undergraduate students, programs, and experiences. This collection of articles gives direction for building undergraduate HRD curricula and enhancing its relevance for traditional college students, identifies relevant competencies for undergraduate HRD programs, and provides insight into alumni perspectives of the value of an undergraduate degree in HRD. The Stakeholders: The primary audience is HRD faculty, scholars, and scholar-practitioners who engage with undergraduate students or hope to in the future. Secondary audiences include human resource management (HRM), management, adult educators, higher education administrators, career counselors, and other professionals who are involved with enhancing the extent to which undergraduate students and new graduates are equipped to make meaningful contributions to organizations.